Approximations of Numerical Method for Neutral Stochastic Functional Differential Equations with Markovian Switching - Hua Yang; Feng Jiang (Journal of Applied Mathematics)
Stochastic systems with Markovian switching have been used in a variety of application areas, including biology, epidemiology, mechanics, economics, and finance. In this paper, we study the Euler-Maruyama (EM) method for neutral stochastic functional differential equations with Markovian switching. The main aim is to show that the numerical solutions will converge to the true solutions. Moreover, we obtain the convergence order of the approximate solutions.